Pentingnya Test of English as a Foreign Language di Era Digital: Juliantina*, Yuni Permatasari - Juliantina; Yuni Permatasari (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
The importance of English proficiency is the key to success in facing the challenges and opportunities in this digital era. In an increasingly connected global work environment, the ability to communicate clearly and effectively in English opens the door to educational, career and cross-cultural collaboration opportunities. Joint efforts from various parties, including the government, educational institutions, and individuals, are needed to improve this situation and prepare Indonesian society for success in an increasingly globally connected digital era. This journal was conducted using qualitative research methods with various other journal sources.